Accounting Information System For Tailoring Materials At Penjahit Ruslan Using The Accrual Basis Method - Sabri, Khairul; Atmaja, Niko Surya; Afrijal, A; Yasdomi, Kiki; Dona, D (IJISTECH (International Journal of Information System and Technology), 2024)
Development of an Accounting Information System (AIS) is crucial for enhancing financial management, particularly for micro and small enterprises (MSEs). This study focuses on implementation of a web-based AIS utilizing the accrual basis method at Penjahit Ruslan, a tailoring business encountering challenges in financial transparency, transaction accuracy, and real-time monitoring. The system, constructed using HTML, PHP, and MySQL, facilitates structured data storage, automated financial reporting, and improved decision-making. Through adoption of UML-based system design and rigorous testing methods, including Blackbox Testing and Performance Testing, AIS ensures high reliability and accuracy in financial recording. Findings indicate that transitioning from manual bookkeeping to a digital financial system significantly enhances efficiency, reduces errors, and strengthens financial oversight. This research contributes to broader digital transformation in financial management for small businesses, offering a scalable solution for enterprises confronting similar challenges.